Effect of Green Tea Mouthwash on Oral Malodor. (2nd December 2012) - Rassameemasmaung, Supanee; Phusudsawang, Pakkarada; Sangalungkarn, Vanida
Abstract : This study aimed to determine the effect of green tea mouthwash on oral malodor, plaque, and gingival inflammation. Gingivitis subjects who had over 80 parts per billion of volatile sulfur compounds (VSC) in the morning breath were randomly assigned into green tea or placebo mouthwash group. At baseline, VSC, Plaque Index (PI) and Papillary Bleeding Index (PBI) were recorded. Participants were rinsed with the assigned mouthwash, and VSC level was remeasured at 30 minutes and 3 hours postrinsing. For the following 4 weeks, participants were asked to rinse with the assigned mouthwash twice daily. VSC, PI and PBI were remeasured at day 28. It was found that, at 30 minutes and 3 hours postrinsing, VSC was reduced by 36.76% and 33.18% in the green tea group and 19.83% and 9.17% in the placebo group, respectively. At day 28, VSC was reduced by 38.61% in the green tea group and 10.86% in the placebo group. VSC level in the green tea group was significantly different when compared to the placebo. PI and PBI were significantly reduced in both groups. However, no significant difference was found between groups. In conclusion, green tea mouthwash could significantly reduce VSC level in gingivitis subjects after rinsing for 4 weeks.